The Relationship Among Ethics and Conflict Management in Hungarian Metal and Machinery Supply Chains - Piricz, Noémi (International Journal of Engineering and Management Sciences, 2016)
It seems that ethics has become an important issue because more and more firms accept ethical codex and make them public as well. On contrary all of us know some stories when unethical behaviour resulted tragedy. Nowadays in business life ethics and responsibility appear as necessary value from the aspect of success. More papers state that ethical behaviour offers various benefits in business relationships. Our paper seeks these positives in empirical way by interviewing members and experts of Hungarian metal and machinery supply chains but we take into consideration the network effects as well. Our survey investigates how fair behaviour can prevent or decrease conflicts in business. The results of our qualitative research show that fair behaviour brings certain benefits but the economic reality and the direction of money flow are dominant. We have met various forms of conflict management and found that respondents want to maintain even very problematic business ties as well.